Peningkatan Kompetensi Mahasiswa melalui Praktik Mengajar Materi Manajemen Pemasaran Pendidikan di UINSI Samarinda : Penelitian - Wahyu, Wahyu Kharisma Murdani; Tamam, Badrut Tamam; Sudadi; Bahrani, Bahrani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the implementation process of learning strategies in the course Educational Service Marketing Management and to analyze students’ level of understanding after participating in learning activities throughout the semester. The project was carried out as part of the Field Study Program involving two classes, MPI 1 and MPI 2, in the third semester of the Islamic Education Management Study Program. This research employed a qualitative descriptive approach supported by simple quantitative data derived from students’ quiz scores. Data were collected through classroom observation, documentation, analysis of assessment results, and student reflections. The learning strategies implemented included interactive lectures, group discussions, presentations, the use of educational institution case studies, and digital assessments through Quizizz. The findings show an improvement in students’ comprehension, indicated by an average quiz score of 75% in MPI 1 and 88% in MPI 2. However, several students remained passive during discussions and lacked a strong conceptual foundation related to educational marketing. Challenges included low participation in asking questions and limited initial understanding of educational branding.